Co-expression of anti-rotavirus proteins (llama VHH antibody fragments) in Lactobacillus: development and functionality of vectors containing two expression cassettes in tandem. - Gökçe Günaydın; Beatriz Alvarez; Yin Lin; Lennart Hammarström; Harold Marcotte (PLoS ONE)
Rotavirus is an important pediatric pathogen, causing severe diarrhea and being associated with a high mortality rate causing approximately 500 000 deaths annually worldwide. Even though some vaccines are currently available, their efficacy is lower in the developing world, as compared to developed countries. Therefore, alternative or complementary treatment options are needed in the developing countries where the disease burden is the largest. The effect of Lactobacillus in promoting health and its use as a vehicle for delivery of protein and antibody fragments was previously shown. In this study, we have developed co-expression vectors enabling Lactobacillus paracasei BL23 to produce two VHH fragments against rotavirus (referred to as anti-rotavirus proteins 1 and 3, ARP1 and ARP3) as secreted and/or surface displayed products. ARP1 and ARP3 fragments were successfully co-expressed as shown by Western blot and flow cytometry. In addition, engineered Lactobacillus produced VHH antibody fragments were shown to bind to a broad range of rotavirus serotypes (including the human rotavirus strains 69M, Va70, F45, DS1, Wa and ST3 and simian rotavirus strains including RRV and SA11), by flow cytometry and ELISA. Hereby, we have demonstrated for the first time that when RRV was captured by one VHH displayed on the surface of co-expressor Lactobacillus, targeting other epitope was possible with another VHH secreted from the same bacterium. Therefore, Lactobacillus producing two VHH antibody fragments may potentially serve as treatment against rotavirus with a reduced risk of development of escape mutants. This co-expression and delivery platform can also be used for delivery of VHH fragments against a variety of mucosal pathogens or production of other therapeutic molecules.